Stability of anthocyanin extracts from tall currant (Ribes altissimum) fruits - Damdindorj, Mungunnaran; Byambaa, Munkhtsetseg; Munkhjargal, Odonchimeg; Barkhuu, Bayarmaa (Mongolian Journal of Agricultural Sciences, 2020)
Plant anthocyanins are colored pigments that are traditionally used as dye and food colorant. Moreover, anthocyanins have been widely studied for its medicinal values and could be potential pharmaceutical ingredients. This study investigated the anthocyanins stability and extraction rate from tall currant extracts. The results showed that tall currant fruits are rich in anthocyanin content, providing 1.93%–2.70% anthocyanin in different extraction solvents. The stability of anthocyanin extracts was significantly affected by light exposure as indicated by 34.96%–56.64% degradation. The optimal condition for anthocyanin extraction from tall currant fruits was achieved with 70% ethanol/citric acid solution (pH = 2.50, and solid/liquid ratio of 1:20) when the extraction was carried out at 70°C for 90 minutes. This condition corresponded to anthocyanin content of 2.39% or 2390 mg anthocyanin in 100 g of dry plant materials. The findings of this study will be useful to predict the quality changes that might occur in preparing food colorants from tall currant (Ribes altissimum) in terms of thermal processing and prevent the degradation of the anthocyanins for the beverage and food industry in Mongolia.